The effect of a light source with reduced irradiance on the marginal seal in class V cavities - Gajić Nataša; Kojić Željka; Đeri Aleksandra; Arbutina Radmila; Trnić Zorica (Serbian Medical Society - Dental Section, Belgrade, 2008)
Introduction: During composite polymerisation, material contraction occurs and leads to microgap formation. Various light sources are used in everyday dental practice for the polymerisation of composite restorations: conventional halogen, xenon, LED light curing units (LCUs) and argon lasers. Aim: The aim of this study was to analyze the effect of an LED LCU with reduced irradiance on the marginal seal of different composite restorations. Material and Method: The study was conducted on 40 extracted human teeth (intact and carious). Class V cavities were prepared on all teeth. Cavities were filled with either Filtek Supreme -3M (20 teeth) or Luksogal - Galenika (20 teeth) and polymerisation was done using an LED source with reduced irradiance (90 mW/cm2). Microleakage was tested using the dye penetration method with silver nitrate. Dye penetration was assessed using a stereo loupe with a microscale and x6 magnification. Results: The obtained results suggested that greater dye penetration occurred in samples restored with Luksogal. There was a statistically significant difference between occlusal (27.00) and gingival (36.90) margins (p<0.05). Dye penetration was observed in all intact and carious teeth restored with Filtek Supreme on both gingival and occlusal margins. A statistically significant difference was observed between gingival (22.90) and occlusal (15.50) margins (p<0.01). Conclusion: Microgaps were observed in all teeth irrespective of the type of composite material used for restoration.